KAJIAN MUNASABAH QS. AL-ḤADĪD AYAT 20–24 SEBAGAI SOLUSI QUR’ANI TERHADAP FENOMENA FOMO - Sidik Amirulloh (LP2M STIK KENDAL, 2025)
The phenomenon of Fear of Missing Out (FOMO) has become one of the most prominent psychological issues in the modern digital culture, marked by anxiety to remain constantly connected and the fear of being left out of social experiences. This article examines QS al-Ḥadīd verses 20–24 through the approach of munasabah to offer a theological framework as a Qur’anic solution to FOMO. This study addresses three questions: how verses 20–24 are interpreted; how the munasabah between these verses constructs a proper life orientation; and how their embedded values can be implemented to reduce FOMO. This research employs a library-based qualitative method by analyzing major tafsīr sources, including the works of ar-Rāzī and Wahbah az-Zuḥaylī, along with supporting literature such as journals, books, and scholarly articles discussing FOMO in the context of modern social life. The findings indicate that verses 20–21 redirect human focus from worldly rivalry toward spiritual musābaqah; verses 22–23 reinforce emotional stability through belief in divine decree; and verse 24 warns of the moral consequences of worldly orientation. The study concludes that the integration of worldly impermanence, righteous competition, belief in qadar, and inner spaciousness forms a comprehensive solution capable of alleviating the psychological roots of FOMO and reorienting human life in the digital age.